ISOLASI DAN IDENTIFIKASI MIKROBA PENDEGRADASI SENYAWA PERSISTEN ORGANIC POLUTTANS PADA TANAH ANDOSOL MAGELANG - Indratin Indratin; Sri Wahyuni; I Made Sudiana (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract-The development of the agricultural sector has resulted in the increase of the environmental pollution by chemicals, such as; persistent organochlorine contaminants, can undergo bioaccumulation in nature. Ramadhani and Oginawati (2009) stated that organochlorine compounds classified as Persistent Organic Pollutants (POPs) are chemical compounds that are persistent in the environment, can undergo bioaccumulation in the food chain, and has the risk of being the cause of many negative impacts on human health and the environment. In the agricultural area, there are microorganisms in the soil that act as decomposers of organic materials or use organic materials as food. This research was conducted at the Microbiology Laboratory of the Research Center for Biology LIPI Cibinong February 2012 to August 2012. Isolation and characterization of microbes degrading Persistent Organic Pollutants (POPs) performed at the Laboratory of Microbiology Research Center for Biology LIPI Cibinong by using three stages, (1) Isolation and identification of POPs degrading microbes, (2) test the growth characteristics of the isolates in the different types of POPs. The purpose of the study is to select the bacteria in the soil that could potentially degrade the insecticide residues that have the characteristics of POPs ( dieldrin , DDT , aldrin , heptaklor ) . The results of bacterial isolation study shows that there are five (5) types of bacteria which are able to degrade POPs ( dieldrin , DDT , aldrin , heptachlor ). Those bacteria are Achoromobacter sp, Catenococcus thiocycli, Heliothrix oregonensis, Bacillus cereus ,Bacillus subtilis. Keywords: soil, isolation, POPs, degrading bacteria